Estimating the costs and perceived benefits of oral pre-exposure prophylaxis (PrEP) delivery in ten counties of Kenya: a costing and a contingent valuation study - Forsythe, Steven; Kioko, Urbanus; Mahiane, Guy; Glaubius, Robert; Musau, Abednego; Gichangi, Anthony; Reed, Jason; Were, Daniel (Frontiers in Reproductive Health, 2024)
Kenya included oral PrEP in the national guidelines as part of combination HIV prevention, and subsequently began providing PrEP to individuals in 2017. However, as scale-up continued, there was a gap in knowledge on the cost of PrEP. The following study calculated the costs of PrEP scale-up as it was being delivered in ten counties in Kenya. This costing also allowed for a comparison of models of service delivery. The analysis was also conducted to understand factors that indicate why some individuals place a greater value on PrEP than others. Data collection was completed between November 2017 and September 2018. Costing data was collected from 44 Kenyan health facilities. Financial and programmatic data were collected from records and through questionnaires. A contingent valuation study was conducted at the same 44 facilities to understand factors that reveal why some individuals place a greater value on PrEP than others. Interviews were conducted with 2,258 individuals (1,940 current PrEP clients and 318 non-PrEP clients). The weighted cost of providing PrEP was 253 per person year, ranging from 217 at health centers to 283 at dispensaries. Drop-in centers (DICEs), which served about two-thirds of the client volume at surveyed facilities, had a unit cost of 276. The largest percentage of costs were attributable to personnel (58.5%), followed by the cost of drugs, which represented 25% of all costs. The median WTP for PrEP was 2/month. This covers only one-third of the monthly cost of the medication (6/month) and less than 10% of the full cost of delivering PrEP (21/month). Certain populations put a higher value on PrEP services, including: FSW and MSM, Muslims, individuals with higher education, persons between the ages of 20 and 35, and households with a higher income and expenditures. This contingent valuation study does have important implications for Kenya’s PrEP program. First, it indicates that some populations are more motivated to adopt PrEP, as indicated by their higher WTP. This suggests that any attempt to increase demand or improve PrEP continuation should consider these differences. Cost recovery from existing PrEP clients would have negative consequences for uptake and continuation.